Minne Elisabeth Allen papers - Allen, Minne Elisabeth
Correspondence, notes and drafts of articles written by Allen, campaign brochures, and newspaper clippings relating chiefly to the 1924 presidential campaign of Progressive Party candidates Robert M. La Follette and Burton K. Wheeler.
Political campaign worker of Ames, Iowa.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: La Follette, Robert M. -- 1855-1925.; Wheeler, Burton K. -- 1882-1975.; Progressive Party (1912); Political campaigns -- Iowa -- Ames; Presidents -- United States -- Election -- 1924.; Campaign workers